Telocytes: An Emerging Component of Stem Cell Niche Microenvironment. (December 2021) - Rosa, Irene; Marini, Mirca; Manetti, Mirko
Telocytes (TCs) are newly identified interstitial cells characterized by thin and long cytoplasmic processes, called telopodes, which exhibit a distinctive moniliform shape and, often, a sinuous trajectory. Telopodes typically organize in intricate networks within the stromal space of most organs, where they communicate with neighboring cells by means of specialized cell-to-cell junctions or shedding extracellular vesicles. Hence, TCs are generally regarded as supporting cells that help in the maintenance of local tissue homeostasis, with an ever-increasing number of studies trying to explore their functions both in physiological and pathological conditions. Notably, TCs appear to be part of stem cell (SC) niches in different organs, including the intestine, skeletal muscle, heart, lung, and skin. Indeed, growing evidence points toward a possible implication of TCs in the regulation of the activity of tissue-resident SCs and in shaping the SC niche microenvironment, thus contributing to tissue renewal and repair. Here, we review how the introduction of TCs into the scientific literature has deepened our knowledge of the stromal architecture focusing on the intestine and skeletal muscle, two organs in which the recently unveiled unique relationship between TCs and SCs is currently in the spotlight as potential target for tissue regenerative purposes.